818 Effectiveness of seasafe lifeguard services in cox's bazar beach Bangladesh. (1st September 2016) - Hossain, Jahangir; Mecrow, Tom; Wills, Steve; Willims, Darren; Rahman, Aminur; Rahman, Fazlur
Abstract : Background: drowning is the leading cause of death among children in Bangladesh and claims the lives of 18, 000 children each year. The southern coastal city Cox's Bazar is one of the largest sandy beaches in the world & has become a popular tourist destination overthe last decade. In 2014 full time Lifeguard services were implemented with the support of RNLI, UK. This presentation describes the effectiveness of the first 6 months lifeguard services in the Cox's Bazar beach. Objective: assessment of the lifeguard services in management of drowning causalities provided by low resource setting lifeguards in Cox's Bazar beach Bangladesh. Methodology: with the support of Royal National Lifeboat Institution (RNLI) the International Drowning Research Centre, Bangladesh (IDRC-B) developed a beach lifeguard program called SeaSafe. Since July 2014, 10 paid lifeguards have been employed to provide lifeguard services on Cox's Bazar beach. All lifeguards were also trained in First aid and CPR to provide support in medical emergencies. To record daily incidents reporting forms and tools were developed. Results: collected data from 25 th of July 2014 to 25 th of January have been analysed. In total 56 causalities were rescued from the sea – 51 male and 5 female. Adolescents were found to be the most vulnerable group. 80% of all rescueswere conducted in the lifeguarded zone, between the red and yellow flags. Nearly 62% of incidence was due to rip currents. About 54% of casualties were using inflatables far from shore before being rescued. Lifeguards used surf boards or rescue tube in 84% of rescues. Among the causalities 88% were not from the Cox's Bazar area. Conclusion: lifeguarding is an essential part of any tourist beach, a lot of lives can be saved by providing lifeguard activities. Further long term research is needed to establish an effective lifeguard system in low resources setting. Acknowledgements: Support of RNLI is acknowledged